Relationship Between Serum Amyloid A1 (SAA1) Gene Polymorphisms Studies with Obesity in the Saudi Population - Alharbi KK (Dove Medical Press, 2021)
Khalid Khalaf Alharbi, Amal F Alshammary, Omar Sammar Aljabri, Imran Ali Khan Department of Clinical Laboratory Sciences, College of Applied Medical Sciences, King Saud University, Riyadh, Saudi ArabiaCorrespondence: Imran Ali KhanDepartment of Clinical Laboratory Sciences, College of Applied Medical Sciences, King Saud University, PO Box-10219, Riyadh, 11433, Kingdom of Saudi ArabiaTel +966501112806Fax +966114693851Email imkhan@ksu.edu.saPurpose: Limited studies have shown positive and negative associations of serum amylase A1 (SAA1) gene in childhood obesity, previously showed the relation with obesity in different ethnicity. The current study therefore investigated the impact of single nucleotide polymorphisms present in the SAA1 gene on subjects of Saudi obesity.Participants and Methods: In this case–control study, we selected 140 subjects of Saudi population and categorized them into 83 cases of obesity and 57 healthy controls. Genotyping was performed with quantitative/real time-polymerase chain reaction in the SAA1 gene for rs11603089A/G, rs4638289A/T and rs7131332A/G polymorphisms.Results: In rs11603089 polymorphism, co-dominant model (AG vs AA+GG; OR-2.23 [95% CI:1.02– 4.86]; p=0.04) and rs4638289 polymorphism, a disparity in significance was observed between the homozygous variant (TT vs AA; OR-16.8 [95% CI: 2.06– 136.8]; p=0.0009), dominant model (AT+TT vs AA; OR-2.57 [95% CI: 1.28– 5.19]; p=0.007), recessive model (TT vs AA+AT; OR-11.36 [95% CI: 1.45– 89.06]; p=0.004) and allelic frequency for (T vs A: OR-2.35 [95% CI: 1.39– 3.98]; p=0.001) between the obesity cases and control subjects. However, statistical correlations did not reveal the rs7131332A/G polymorphism either (p> 0.05).Conclusion: In conclusion, rs4638289 polymorphism was associated with risk allele and dominant model with obesity subjects. Further additional studies were warranted.Keywords: obesity, SAA1 gene, rs11603089, rs4638289 and rs7131332 polymorphisms